Continuous Intraoperative Nerve Monitoring in Thyroid Surgery: Can Amplitude Be a Standardized Parameter? - Mazzone, Sara; Esposito, Adelaide; Giacomarra, Vittorio (Frontiers in Endocrinology, 2021)
The objective of this study is to evaluate electromyographic waveforms related to vagus monitoring. We collected data from patients undergoing thyroidectomy with CIONM, regardless of vocal cord response amplitude initially measured. We divided data of 193 nerves into three groups, according to initial amplitude value: ≥500 µV (Group 1,110 pt.), between 100 and 500 µV (Group 2, 79 pt.), and <100 µV (Group 3, 4 pt.). ROC curve showed a high diagnostic accuracy of final amplitude absolute value in vocal cord paralysis detection in both groups (89 and 86%). An increase of vocal cord paralysis risk was associated with progressive amplitude reduction (Group 1: OR=1.05, CI=1.02–1.09, p=0.001; Group 2: OR=1.05, CI=1.02–1.08, p=0.002). Cut-off values for amplitude reduction with optimal sensitivity and specificity were −77% in Group 1 and −15% in Group 2. In Group 3 signals showed an amplitude <100 µV for all monitoring, with no loss of a recognizable signal and normal postoperative cordal functionality. The use of a strict amplitude signal cut-off value ≥500 µV could be too restrictive. Also, signal with baseline amplitude <500 µV may be considered equally adequate. Setting the alarm for a reduction of 77% in patients with initial amplitude ≥500 µV and of 15% for those <500 µV could make monitoring safe and an effective aid for surgeons. In conclusion, there are cases in which initial amplitude is lower than that considered as adequate by current literature but with well recognizable and stable EMG waveforms. How those cases should be approached and what should the surgeon’s attitude be are a matter of discussion.